Strategic management techniques to manage communal property in Mykolayiv region - Кошкин, Константин Викторович; Макеев, Сергей Авоезиевич; Михелев, Игорь Леонидович; Фоменко, Георгий Вадимович (Eastern-European Journal of Enterprise Technologies, 2012)
Identify and analyse the main challenges in managing public assets in Ukraine and their impact on investment potential the Mykolayiv region